Peran Fikih dalam Mengatur Pergaulan Remaja Masa Kini - Muh Yusuf; Muhammad Zuhdi Hibatullah; Alawiyah Nabila; Nur Hasyikin; Muhammad Yasin (Yayasan Literasi Sains Indonesia, 2023)
This research explores the critical role of Fiqh (Islamic jurisprudence) in guiding and regulating the social interactions of contemporary adolescents. Drawing on historical narratives in the Islamic tradition and emphasizing the importance of Fiqh in addressing challenges such as juvenile delinquency, the research underscores the need for practical application of Fiqh principles in everyday life. It argues that Fiqh education, which goes beyond theoretical understanding, entails the practical implementation of acquired knowledge, integrating theory and action. This study uses the literature research method, reviewing relevant literature to analyze the concept of adolescent social interaction from an Islamic fiqh perspective. The findings indicate a mismatch between Islamic values and current teenage trends, including changes in dressing styles, an increase in premarital relationships, drug abuse, and materialistic pursuits. The paper suggests the need for guidance from adolescents and parents to bridge the gap between Islamic principles and contemporary trends, emphasizing the importance of fiqh education in adolescence as a basis for navigating life in accordance with Islamic values.